2020
DOI: 10.1097/bsd.0000000000000968
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Various “Myelopathic Symptoms” in Cervical Myelopathy

Abstract: Study Design: A retrospective cohort of prospective data. Objective: Determine the frequency of various symptoms in a surgical cohort of cervical myelopathy (CM). Summary of Background Data: CM can be difficult to diagnose as there is no sine qua non “myelopathic symptom.” Despite extensive literature, the likelihood or frequency of symptoms at presentation remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Segmental spinal cord compression can cause local impairment of the spinothalamic tract at its chiasma at the central grey matter of the spinal cord [20]. Irrespective of the precise cause, a large-scale cohort study revealed that cervical myelopathy can cause neck pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…Segmental spinal cord compression can cause local impairment of the spinothalamic tract at its chiasma at the central grey matter of the spinal cord [20]. Irrespective of the precise cause, a large-scale cohort study revealed that cervical myelopathy can cause neck pain [21].…”
Section: Discussionmentioning
confidence: 99%
“…Segmental spinal cord compression can cause local impairment of the spinothalamic tract at its chiasma at the central grey matter of the spinal cord 21 . Irrespective of the precise cause, a large-scale cohort study revealed that cervical myelopathy can cause neck pain 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Across several studies, the sensitivities of bladder dysfunction for diagnosis DCM ranged from 4% to 68% with a weighted average of 38% (95% CI 34%-43%). Other studies did not distinguish between bladder and bowel dysfunction and either reported the frequency of sphincter disturbance (7%-100%) 21,40,48,50,54,57,59 or of bladder and/or bowel dysfunction (5%-30%). 20,26,38,39,42,43,61,62,71 Three studies reported the frequency of sexual dysfunction in a cohort of DCM patients.…”
Section: Symptoms Related To Hand and Upper And Lower Extremitymentioning
confidence: 99%
“…30,31,71 Symptoms Related to Pain. Several studies reported on the frequency of various types of pain in patients with DCM: radicular or radiating (n = 12), 20,24,25,31,34,48,49,59,61,66,67,75 neck and/or shoulder (n = 27), 20,23,25,28,[30][31][32][34][35][36]42,46,47,49,[51][52][53][54]56,57,61,64,65,67,71,73,74 upper extremity (n = 5), 26,36,52,57,65 axial (n = 5), 27,40,44,65,72 back (n = 2) ...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation